PENGARUH PERSEPSI MANFAAT, PERSEPSI KEMUDAHAN DAN PERSEPSI KEAMANAN TERHADAP PENGGUNA E-WALLET PADA MASYARAKAT DI KOTA SEMARANG - Harminingtyas, Rudika; Susetyarsi, Th. (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2022)
This study aims to determine the effect of perceived benefits, perceived convenience, and perceived security on the decision to use e-wallets among people in the city of Semarang. The population in this study are people in the city of Semarang who use the e-wallet application as a transaction tool. The sampling technique used in this study used a snowball and obtained 90 respondents. Data collection method with questionnaires distributed online. The analytical tool in this study is multiple linear regression analysis. The results show that perceived benefits, perceived convenience, and perceived security have a positive and significant effect on the decision to use e-wallet in the people of Semarang City. The perceived security variable has a dominant influence on the decision to use e-wallet. Security is indeed the most important in the decision to use an e-wallet because someone feels safe and protected.Keywords: Perceived Benefit, Perceived Convenience, Perceived Security, E-Wallet